(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Relevance: Various indexing systems play an important role for dentists in assessing the condition of hard dental tissues and conducting scientific epidemiological studies. Among these systems, identifying the most effective indices remains an аctual issue in modern dentistry. Objective: To conduct a comparative analysis of the dmft, ICDAS-II, and CAST indices in evaluating the condition of primary teeth in preschool children. Materials and Methods: The study included 315 children aged 3–6 years attending state preschool educational institutions in the Tashkent region. A clinical epidemiological examination was performed using the dmft, ICDAS-II, and CAST indices to assess dental caries in primary teeth. Results: The mean caries intensity among children aged 3–6 years was 4.16 ± 0.23 according to the dmft index, while the values obtained using CAST and ICDAS-II were 4.85 ± 0.24 and 5.47 ± 0.24, respectively. Conclusion: A high prevalence and intensity of dental caries were observed among children aged 3–6 years. Comparative analysis of the assessment indices demonstrated that ICDAS-II and CAST systems provide more detailed detection of early caries lesions and allow deeper analysis of the stages of tooth damage compared with the traditional dmft index.